Answer:
Marry = $17
Ravi = $11
Alan = $34
Explanation:
Let us assume
Mary be X
Ravi be Y
Alan be Z
So, the equation in total is
X + Y + Z = 62
It is given that
X = Y + 6
Z = 2X
Now we put the Z value in the total equation, so it would be
X + Y + 2X = 62
3X + Y = 62 .................................... (1)
And can we write
X = Y + 6
X - Y = 6 ................................. (2)
Now substitution these two equations,
3X + Y = 62
X - Y = 6
2X = 68
X = $17
So, Z = 2 × 17 = $34
And, Y
$17 + Y + $34 = $62
So, Y = $11